2014
DOI: 10.1103/physrevlett.112.077205
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antiferromagnetic Ordering in the (1×2) Surface Reconstruction ofCa(Fe1x

Abstract: Low energy electron diffraction, scanning tunneling microscopy and spectroscopy, and first-principles spin-dependent density functional theory are utilized to investigate the geometric, electronic, and magnetic structures of the stripe-ordered (1×2) surface of Ca(Fe1-xCox)2As2 (x=0, 0.075). The surface is terminated with a 50% Ca layer. Compared to the bulk, the surface Ca layer has a large inward relaxation (∼0.5  Å), and the underneath As-Fe2-As layer displays a significant buckling. First-principles calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…2d is ~0.7 Å shorter than the corresponding bulk spacing between Ca2 and Pt1 (1.67 Å). This STM result is consistent with the behavior reported at the surface of CaFe 2 As 2 with 0.5 ML Ca coverage20, where Ca atoms are pulled down by ~0.5 Å (~30%) determined by low energy electron diffraction (LEED). In addition, the calculated charge states using the Bader scheme in ref.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…2d is ~0.7 Å shorter than the corresponding bulk spacing between Ca2 and Pt1 (1.67 Å). This STM result is consistent with the behavior reported at the surface of CaFe 2 As 2 with 0.5 ML Ca coverage20, where Ca atoms are pulled down by ~0.5 Å (~30%) determined by low energy electron diffraction (LEED). In addition, the calculated charge states using the Bader scheme in ref.…”
Section: Resultssupporting
confidence: 90%
“…5b) exhibits a finite zero bias conductance (ZBC). Such a feature has been observed previously in other Fe-based superconductors20212223242526, even when probed at much lower temperatures than their T c , indicating the ZBC is not due to the thermal broadening effect. It was also shown that spectral features can vary on different reconstructed surfaces in BaFe 2−x Co x As 2 26 suggesting reconstructions may be closely related to the observed ZBC in Fe-based superconductors.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…As a result the region adjacent to the cleaved surface, the selvedge 4 , differs both chemically and structurally from the bulk. The remaining surface Ba atoms surfaces 12 . Either an uneven distribution of the Ba adatoms, or structural distortions in the surface lattice (or a combination of the two) may lead to a modified doping and changes in the superconductivity in the selvedge.…”
mentioning
confidence: 99%